Developmental education for innovation: lessons from an experience in Kenya. (1st January 2013) - Adwera, Andrew; Hanlin, Rebecca; Johnson, Hazel
Promoting innovation through education is a challenge for both advanced industrial and developing economies. The linkages between public and private investment in education, the kind of education that is needed and sources of social and economic dynamism are all-important. These linkages are particularly challenging in the Global South, where many types of dynamism and social need are 'below the radar'. This is the backdrop to a practice-based project that used training in technology policy and innovation research to promote employability and innovation capability in key sectors in Kenya. We use findings from surveys, interviews, workshops and stakeholder meetings to rethink the role of education and training in supporting innovation that focuses on social need. We contribute to debate by arguing for a developmental education system based on a multi-sector and multi-organisational approach, and which combines different types of education, training and learning in collaboration with public and private sector enterprise.